A rare case of early onset nephrotic syndrome in pregnancy - (:unkn) unknown (My University, 2006)
Nephrotic syndrome occurs very rarely, about 0.012-0.025% of all pregnancies. Here, we report a rare case of early onset nephrotic syndrome developing de novo in the 17th week of pregnancy. A renal biopsy was done and the specimens revealed typical features of focal segmental glomerulosclerosis. The patient had a progressive clinical course of disease despite steroid treatment. Suffering from severe intrauterine growth restriction, the fetus died in utero. After delivery, steroid treatment was continued. The patient had normal renal function with a decrease in proteinuria in the second and fifth month postpartum. This report points out the poor fetal prognosis associated with an early onset nephrotic syndrome. Pregnant patients with early onset nephrotic syndrome should be carefully evaluated for the presence of chronic renal disease, and primary renal pathology should be included in the differential diagnosis of massive proteinuria in early pregnancy.
Keywords: Adult; Female; Humans; Pregnancy; Glucocorticoids; Pregnancy Complications; Antihypertensive Agents; Kidney; Hypertension, Pregnancy-Induced; Fetal Death; Angiotensin-Converting Enzyme Inhibitors; Prednisolone; Diet, Sodium-Restricted; Methyldopa; Nephrotic Syndrome